Digital Transformation and Employee Performance: The Mediating Role of Organizational Commitment and the Moderating Role of Organizational Culture in the Indonesian Public Sector - Anggun Kurnia Dewi; Riswan (International Journal of Economics, Business and Innovation Research, 2026)
Digital transformation has become a strategic requirement for improving bureaucratic effectiveness, yet its success is strongly influenced by human and cultural factors. This study analyzes the effect of digital transformation on employee performance with organizational commitment as a mediator and organizational culture as a moderator at the Secretariat of the Regional House of Representatives (DPRD) of Pesisir Barat Regency, Indonesia. The study employs a quantitative explanatory survey of 68 employees and analyzes the data using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analytical framework is grounded in the Resource-Based View (RBV) and Behavioral Perspective to explain the role of digital capabilities, employee attitudes, and organizational values. The results show that digital transformation has a positive and significant effect on employee performance, both directly and indirectly through organizational commitment. Meanwhile, organizational culture weakens the effect of digital transformation on performance. These findings extend the literature on digital transformation in the public sector by integrating mediation and moderation mechanisms within a single empirical model in a legislative institution context in Indonesia.